The relationship between metabolic dysfunction‐associated fatty liver disease and low muscle mass in an asymptomatic Korean population. Issue 6 (12th October 2022) - Seo, Ji Yeon; Cho, Eun Ju; Kim, Min Joo; Kwak, Min‐Sun; Yang, Jong In; Chung, Su Jin; Yim, Jeong Yoon; Yoon, Ji Won; Chung, Goh Eun
Abstract: Background: Metabolic (dysfunction)‐associated fatty liver disease (MAFLD) emphasizes the metabolic dysfunction in nonalcoholic fatty liver disease (NAFLD). Although the relationship between low muscle mass and NAFLD has been suggested, the effect of MAFLD on low muscle mass is yet to be investigated. In this study, we examined the relationship between MAFLD and low muscle mass in an asymptomatic Korean population. Methods: Examinees who underwent FibroScan® and bioelectrical impedance analyses on the same day during the period of June 2017 to December 2019 were included. Hepatic steatosis was diagnosed using controlled attenuation parameter (CAP) with two cut‐off values of 248 and 294 dB/m. Low muscle mass was defined based on appendicular skeletal muscle mass/body weight (wt) or body mass index (BMI) ratios of two standard deviations below the sex‐specific mean for healthy young adults. Subjects were divided into four subgroups: diabetic MAFLD (presence of diabetes mellitus [DM]), metabolic dysfunction (MD) MAFLD (≥2 metabolic abnormalities without DM), overweight MAFLD (overweight/obese without DM and <2 metabolic abnormalities) and no MAFLD. Results: Among all of the 6414 subjects (mean 53.9 years of age; 85.4% male), the prevalence of MAFLD was 49.9% and 22.7% for CAP cut‐off values of 248 and 294 dB/m, respectively. In the multivariate analysis, MAFLD was associated with an increased risk of both low muscle mass_wt (odds ratio [OR] 1.80, 95% confidence interval [CI] 1.38–2.35, P  < 0.001) and low muscle mass_BMI (OR 1.31, 95% CI 1.01–1.70, P  = 0.042). The risk of low muscle mass_wt and low muscle mass_BMI increased the most in the diabetic MAFLD subgroup compared with the no‐MAFLD group (OR 2.11, 95% CI 1.51–2.96, P  < 0.001 and OR 1.51, 95% CI 1.08–2.13, P  = 0.017). There was an increased risk of low muscle mass_wt in the MD MAFLD subgroup (OR 1.73, 95% CI 1.31–2.28, P  < 0.001). Comparable results were observed when the CAP cut‐off value of 294 dB/m was applied. Conclusions: The presence of MAFLD is significantly associated with increased risk of low muscle mass with varying risks according to the MAFLD subgroups. Clinicians should be aware of the differentiated risk of low muscle mass across the subgroups of MAFLD.